Physiological responses to ball-drills in regional level male basketball players - Castagna, C.; Impellizzeri, F. M.; Chaouachi, A.; Abdelkrim, A. B.; Manzi, V. (Journal of Sports Sciences, 2011)
The main aim of this study was to assess the physiological responses of male basketball players during usual basketball ball-drills. Fourteen male basketball players (age 18.9 ± 2.3 years) performed the following full-court (28 × 15 m) basketball ball-drills (3 × 4-min with 3-min passive rest): five-a-side (5v5), three-a-side (3v3) and two-a-side (2v2). A main effect (P < 0.0001) for ball-drills modes was evident for all variables (5v5 < 3v3 < 2v2). Mean [Vdot]O2 during the 5v5, 3v3 and 2v2 were 39.0 ± 7.2, 42.0 ± 7.5 and 45.0 ± 6.5 ml · kg-1 · min-1 (69 ± 11, 74 ± 12 and 79 ± 11% of [Vdot]O2peak) respectively (5v5 = 3v3 < 2v2, P < 0.001). Mean blood-lactate concentrations for 5v5, 3v3 and 2v2 were 4.2 ± 1.8, 6.2 ± 2.3 and 7.8 ± 1.2 mmol (l-1 respectively (5v5 < 3v3 < 2v2, P < 0.01). During the 5v5, 3v3 and 2v2 mean heart-rate (HR) was 84.0 ± 9.2, 88.0 ± 8.4 and 92.0 ± 5.6% of the individual peak respectively (5v5 < 3v3 < 2v2; P < 0.001). No significant differences were found between the regression-line slope (P = 0.86) and intercept (P = 0.45) of the HR-[Vdot]O2 relationships of the multistage maximal fitness test (r2 from 0.80 to 0.96, P < 0.001) and ball-drills (r2 from 0.70 to 0.95, P < 0.001) conditions. Reducing the number of players over the same playing court resulted in increments in physiological demands. The 2v2 condition provided responses in the range of those reported to improve aerobic and anaerobic fitness. The aerobic demands of ball-drills can be accurately assessed using heart-rate monitoring in basketball.